2019
DOI: 10.1136/sextrans-2019-054156
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare providers and community perspectives on expedited partner therapy (EPT) for use with gay, bisexual and other men who have sex with men

Abstract: ObjectivesExpedited partner therapy (EPT) is an effective strategy to reduce rates of chlamydia and gonorrhoea infection and ensure sexual partners are treated. Currently, EPT is provided to heterosexual patients; however, EPT is not routinely recommended for use with gay, bisexual and other men who have sex with men (GBMSM) because of concerns about HIV coinfection. The objective of the qualitative study was to understand provider and community views on the use of EPT with GBMSM.MethodsUsing convenience sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…This study also identified unique barriers to antibiotic overuse in presumptive or symptomatic treatment without laboratory confirmation, as well as concern for increasing traffic to the ED for STI patients. 23,24…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study also identified unique barriers to antibiotic overuse in presumptive or symptomatic treatment without laboratory confirmation, as well as concern for increasing traffic to the ED for STI patients. 23,24…”
Section: Discussionmentioning
confidence: 99%
“…We developed a 21-item survey instrument (Appendix X) including the following sections: demographics, knowledge, attitudes, and behaviors, followed by barriers and facilitators of EPT implementation. The survey instrument was created following a published framework for developing questionnaires 21 and began with discussions with EPT content experts alongside a literature review of published manuscripts on EPT implementation in other practice settings, [22][23][24][25] after which new questions were developed as necessary. We refined the design and content in an iterative process-editing survey versions as needed after each step -through the following steps: (1) a discussion with a survey methodologist expert;…”
Section: Survey Developmentmentioning
confidence: 99%
“…We built on work identifying barriers and facilitators to EPT provision by estimating how proposed policy alternatives might increase the number of partners treated. 8,18,19 As the number of partners treated with EPT increased, partners treated in simple partner referral decreased, which could reduce the number of partners who would receive STI testing. Successful partner referral may be more effective at only treating those partners who are positive for chlamydia, but EPT has the potential to reach more partners who would not otherwise seek testing and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have identified gaps at the provider, clinic, pharmacy, and patient levels, including clinician and pharmacist awareness of laws and knowledge about EPT prescribing and dispensing, lack of standard protocols and counseling to streamline evidence-based patient care, and access barriers for patients, such as cost. [10][11][12] Provider's uptake and offer of EPT are often rate-limiting steps, 13 highlighting the possible benefit of centralizing STI notification and EPT counseling and provision among experienced clinicians and care sites. In this quality improvement (QI) initiative, we aimed to address identified barriers to offering and provision of EPT across 3 care settings.…”
mentioning
confidence: 99%